Acute glomerulonephritis in children: a hospital-based study in a tertiary care centre in Nepal - Adhikari, Sudhir; Sitaula, Deekshanta; Regmi, Shanti; Parajuli, Biraj; Poudel, Sumita (Journal of Chitwan Medical College, 2022)
Background: Acute glomerulonephritis is a common pediatric kidney disease which places a huge burden in developing countries. This study aimed to evaluate causes, clinical manifestations, laboratory findings and complications of acute glomerulonephritis in children presented to a tertiary care center of Nepal. Methods: This was a retrospective review of records of children admitted with acute glomerulonephritis at Chitwan Medical College from April 2018 to February 2021. Socio-demographic data, clinic-laboratory profile and outcomes were obtained from medical records and descriptive analysis was carried out. Results: Among 48 recruited children with acute glomerulonephritis, 60.4% were male and the mean age was 9.5 ± 3.7 years. Post infectious glomerulonephritis including post streptococcal glomerulonephritis (48%) was the main cause of acute glomerulonephritis. The major clinical features were edema (81.3%), hypertension (72.9%), dyspnea (29.2%) and hematuria (25%). ASO titer was positive in 45.8%. The complications noted were acute kidney injury (6.3%), hypertensive emergency (6.3%) and congestive cardiac failure (2.1%). Conclusions: Most of the patients were above 5 years of age and presented most commonly during autumn and summer season. The complications of acute glomerulonephritis were acute kidney injury, hypertensive emergency and congestive cardiac failure.